REPRESENTASI OF DA’WAH MESSAGES THROUGH PAINTINGS; ANALYSIS OF DA’WAH ISLAMIC DA’WAH IN SUFISTIK PAINTINGS @_ ZUKKK WITH A SEMIOTIC APPROACH - romadlany, zakiyah; Ahmad Kavin Billah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
Painting is an art form of beauty has become increasingly crucial to convey Islamic messages and values in the new digital, da’wah media in the digital era, indicating in broadcasting Islam with various forms of methods, one of which is through painting (sign). This digital da’wah is a trend in society, especially the younger generation, the tendency to learn religion through social media. This research investigates the role of paintings in Islamic preaching. taking a case study of paintings on artists on the Instagram account "@_Zukkk". This research aims to analyze how the art by Zukkk plays an important role to starting da'wah in a unique way to convey Islamic values and its impact on viewers' understanding and interaction on the Instagram. This research used by Roland Barthes' semiotic study, which is a continuation of Saussure's thought in introducing the concept of connotation and denotation is the key to analysis. The results show that Zukkk's paintings have a very crucial role in da’wah Islam using a unique way. Through the expression of painting, Zukkk succeeds in providing Islamic messages, such as kindness, justice, patience, to inspiring his followers. Positive responses and powerful interactions, the many people who use the Instagram platform indicate the effectiveness of painting as a medium for delivering da’wah. The paintings are able to motivate the audience.   Keywords: Dakwah, Painting, Instagram, Semiotics